2014
DOI: 10.2147/nss.s59317
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea in children with refractory monosymptomatic nocturnal enuresis

Abstract: BackgroundChildren with nocturnal enuresis (NE) are believed to have deep sleep with high arousal threshold. Studies suggest that obstructive sleep apnea–hypopnea syndrome (OSAHS) and NE are common problems during childhood. We sought to assess the prevalence of OSAHS in children with refractory NE and whether its severity is associated with the frequency of bedwetting.MethodsThe study group comprised 43 children with refractory monosymptomatic NE and a control group of 30 children, both aged 6–12 years. All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Nocturnal secondary enuresis, defined as nighttime incontinence, which emerges after at least 6 months of continence, is also suggestive of SDB. (12)…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…Nocturnal secondary enuresis, defined as nighttime incontinence, which emerges after at least 6 months of continence, is also suggestive of SDB. (12)…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…Our study further confirmed a high prevalence of OSA in patients with MNE (21.9%) as compared to the general pediatric population (8.9%). Moreover, previous studies have also shown a significant higher rates of OSA in patients with refractory nocturnal enuresis[ 23 ]. Thus, the study findings suggests that it is imperative to screen the children with MNE for the presence of symptoms of OSA by appropriate scales, as the patients of MNE with concomitant OSA may require different therapeutic interventions.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Alexopoulos, et al found that NE was associated significantly with presence of moderate-to-severe OSA after adjustment for tonsillar hypertrophy, obesity, gender, and age (adjusted odds ratio = 1.92 (1.08–3.43); P = 0.03). Another study using overnight polysomnography in 43 children with MNE against 30 controls reported, higher prevalence of OSA in children with refractory NE[ 23 ]. Waleed, et al in a hospital based study, diagnosed sleep disordered breathing in 30.4% of enuretic children with a downgrade trend of enuresis and SRBD with increasing age[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many parents consider it a normal behaviour during sleep in childhood. Further nocturnal symptoms are profuse sweating, which may be related with laboured breathing, and nocturnal secondary enuresis, very pathognomonic for severe OSAS [ 30 ]. Night terror and sleepwalking during slow-wave sleep may occur in children and adolescents with a positive family history of parasomnias [ 31 ].…”
Section: What Is the Role Of Alternative Diagnostic Tools In The Diag...mentioning
confidence: 99%